2015
DOI: 10.1017/iop.2015.26
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Response Effort Across Sample Types: Perception or Reality?

Abstract: Landers and Behrend (2015) question organizational researchers’ stubborn reliance on sample source to infer the validity of research findings, and they challenge the arbitrary distinctions researchers often make between sample sources. Unconditional favoritism toward particular sampling strategies (e.g., organizational samples) can restrict choices in methodology, which in turn may limit opportunities to answer certain research questions. Landers and Behrend (2015) contend that no sampling strategy is inherent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Moreover, evidence of unidimensionality improved and coefficient alpha increased slightly after removing respondents flagged for IER (Huang et al., ), and coefficient alpha and multiple regression R 2 values were higher for attentive respondents (Maniaci & Rogge, ). Despite this evidence and perceptions that IER has moderate impacts on survey results (Liu, Bowling, Huang, & Kent, ), the use of IER detection methods is rare in published research (Ran, Liu, Marchiondo, & Huan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, evidence of unidimensionality improved and coefficient alpha increased slightly after removing respondents flagged for IER (Huang et al., ), and coefficient alpha and multiple regression R 2 values were higher for attentive respondents (Maniaci & Rogge, ). Despite this evidence and perceptions that IER has moderate impacts on survey results (Liu, Bowling, Huang, & Kent, ), the use of IER detection methods is rare in published research (Ran, Liu, Marchiondo, & Huan, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative to have similar, reliable, and valid sample sizes. To deem a study valid, results must be similar among multiple samples regardless of sampling strategies (Ran, Liu, Marchiondo, & Huang, 2015). Online studies have been shown to typically have a higher level of carelessness and insufficient effort responding than paper and pencil studies (Huang, Bowling, Liu, & Li, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As noted, organisational researchers generally do not report treatment of IER in published studies (Ran et al, ). This may reflect an overall inattention to the issue of IER (see Liu et al, ), or simply reflect researchers’ omission in reporting such screening.…”
Section: Discussionmentioning
confidence: 99%
“…Liu, Bowling, Huang, and Kent () surveyed Society for Industrial and Organizational Psychology members and results indicated that only 37 per cent reported checking for IER “a lot” or “almost all the time”. Ran, Liu, Marchiondo, and Huang () examined data‐screening procedures pertaining to IER detection for articles published from 2012 to 2014 in the Journal of Applied Psychology , Journal of Management , and Academy of Management Journal , and found that IER screening procedures were reported in only three of 463 survey data samples.…”
Section: Introductionmentioning
confidence: 99%